Assessment of "Green" Economy Development in Regions (on the Example of the Republic of Kazakhstan) - Varavin, Evgeny Vladimirovich; Kozlova, Marina Vasilyevna (Economy of Regions, 2018)
A lack of practice in assessing sustainable development of Kazakhstan regions for effective territory policy has necessitated studying the experience of environmental and economic indicators application into accounting. The article deals with the assessment of the regional green economy development at the meso level using integral indicators. The recommended practice is based on the approach of applying an environmental and economic indicator in Russia. ms approach is based on the World Bank principles for developing the indicator of adjusted net savings. The official statistics of the socio-economic and ecological status of the regions in the Republic of Kazakhstan in 2006-2015 became background of this research. According to the calculations, we have grouped the Kazakhstan regions into three ecological categories. We propose to compare the formed groups with the classification of Kazakhstan regions by the level of economic development taking into account innovative activity, degree of human capital development, regional accessibility and concentration of business as well as the regional gross product per capita. To group regions, we used hierarchical cluster analysis and the Ward’s method. The research findings have revealed the relationship between the level of economic development of the country’s regions and their environmental situation. Пе majority of regions focused on the industrial development have an average indicator of adjusted net savings. Oil-producing regions have a distinctly negative rate. At the same time, agrarian regions have a high and above the average values of adjusted net savings. Empirical conclusions of this research can be used for developing effective environmental and innovation regional policies. Wius, according to the results of the analysis, we recommend to avoid destructive projects with strong environmental impact in those Kazakhstan’s regions, which have the high values of the index of adjusted net savings and possess the enormous potential of ecosystem services and biodiversity. In the regions with low values, we recommend to increase investment in the implementation of eco-innovation projects and to diversify production in order to reduce the level of ecological loads.